Server‐aided batch verification signature schemes in the multiple‐signer setting. Issue 11 (15th April 2013) - Wang, Bin; Zhao, Qing
ABSTRACT: Server‐aided verification (SAV) signature schemes are useful for power‐constrained devices since a powerful server can assist in performing costly operations such as pairing operations. Wu et al . defined security notions for SAV signature schemes and constructed SAV protocols for some existing signature schemes. We extend their work by introducing a new notion called server‐aided batch verification (SABV) signature schemes, which allows signatures on (possibly) different messages by (possibly) different signers to be simultaneously verified with the help of an honest server. Then, we define completeness, soundness, and existential unforgeability for SABV signature schemes in the multiple‐signer setting. In the following, we design SABV protocols for Waters signature and Boneh–Lynn–Shacham signature, respectively, and prove that these protocols meet the requirement of soundness defined in this paper. Finally, we evaluate the performance of the proposed SABV protocols to show that the cost of a verifier can be further reduced compared with the corresponding SAV protocols presented by Wu et al . Copyright © 2013 John Wiley & Sons, Ltd. Abstract : Our SABV schemes allow signatures on different messages by different signers to be simultaneously verified with the help of an honest server. We design SABV protocols for Waters signature and BLS signature respectively and prove that these protocols meet the requirement of soundness. The result shows that the cost of a verifier in our SABV protocols can be further reduced compared with the corresponding SAV protocols.